Criminalising the denial of serious international crimes in Finland: A significant change or mere symbolism? - Karkkulainen, Jussi (Nordisk Tidsskrift for Kriminalvidenskab, 2025)
Abstract In Finland, the government has proposed the addition of a new Section 10b to Chapter 11 of the Criminal Code, under which a person would be criminally liable if they publicly deny, condone or grossly trivialise genocide, crimes against humanity, the crime of aggression, or war crimes as established by a final judgment of an international court, in a manner conducive to inciting violence or hatred against a group protected under the provision on agitation against a population group, and conducive to disturbing public order. Whereas Sweden introduced a similar provision criminalising the denial of a serious international crime in 2024, the criminal codes of Denmark and Norway do not contain such a provision. In this article, I examine the extent to which the legislative reform will change the scope of punishable hate speech in Finland. I approach my research question by analysing the current legal framework through preparatory legislative materials and especially case law concerning agitation against a population group. In this way, I examine what kinds of acts related to the denial of serious international crimes have already been punishable under the existing provision on agitation against a population group. I then analyse, based on the government proposal, which acts will become punishable under the new provision. The denial, justification or gross trivialisation of international crimes appeared only rarely in the research material. Such statements were often embedded in broader expressions targeting Jews, immigrants, or people of colour, making it difficult to assess whether the denial itself would have been punishable under previous legislation. However, since the denial, condoning or gross trivialisation of a serious international crime must be carried out in a manner conducive to inciting violence or hatred and conducive to disturbing public order, denial alone will not be punishable under the new provision either. The new offence has been narrowly defined to protect freedom of expression and to uphold the principle of legality. While this approach avoids penalising, for example, scientific discussion of historical events, it also sets a high threshold for criminal liability. As a result, acts that will be punishable under the new provision have, as a general rule, already fallen within the scope of criminal liability under the previously applicable law. In the future, such acts would merely be prosecuted under a different offence title. Thus, the significance of the new criminalisation lies primarily in its symbolic value and in providing greater legal clarity. Sammandrag I Finland har regeringen föreslagit att ett nytt 10 b § ska fogas till 11 kap. i strafflagen. Enligt förslaget ska den som på ett sätt som är ägnat att uppmana till våld eller hat mot en i 10 § avsedd grupp eller en medlem av gruppen och att störa den allmänna ordningen offentligen förnekar, ursäktar eller allvarligt förringar ett sådant folkmord, ett sådant brott mot mänskligheten, ett sådant aggressionsbrott eller en sådan krigsförbrytelse som fastställts genom ett lagakraftvunnet avgörande av en erkänd internationell domstol, dömas för förnekelse av allvarligt internationellt brott till böter eller fängelse i högst två år. Medan en bestämmelse som kriminaliserar förnekelse av allvarliga internationella brott trädde i kraft i Sverige år 2024, saknas motsvarande bestämmelser i Danmarks och Norges strafflagar. I denna artikel undersöker jag i vilken utsträckning den föreslagna lagändringen kommer att påverka omfattningen av straffbar hatretorik i Finland. Forskningsfrågan behandlas genom en analys av den gällande rättsliga regleringen med stöd av förarbeten och särskilt rättspraxis rörande hets mot folkgrupp. På detta sätt analyserar jag vilka gärningar som hänför sig till förnekelse av allvarliga internationella brott som redan har varit straffbara enligt den nuvarande bestämmelsen om hets mot folkgrupp. Därefter analyserar jag, med utgångspunkt i regeringens proposition, vilka gärningar som kommer att omfattas av straffansvar enligt den nya bestämmelsen. Förnekelse, ursäktande eller allvarligt förringande av internationella brott förekom endast sällan i forskningsmaterialet. Sådana uttalanden var ofta inbäddade i bredare uttryck riktade mot judar, invandrare eller personer med utländsk bakgrund, vilket försvårade bedömningen av om själva förnekelsen hade varit straffbar enligt tidigare lagstiftning. Eftersom förnekelse, ursäktande eller allvarligt förringande av ett allvarligt internationellt brott enligt förslaget måste ske på ett sätt som är ägnat att uppmana till våld eller hat och att störa den allmänna ordningen, kommer inte heller förnekelse i sig att vara straffbar enligt den nya bestämmelsen. Den nya straffbestämmelsen har utformats snävt i syfte att skydda yttrandefriheten och upprätthålla legalitetsprincipen. Medan denna lösning undviker att kriminalisera exempelvis vetenskaplig diskussion om historiska händelser, innebär det också en hög tröskel för straffansvar. Följaktligen har gärningar som kommer att vara straffbara enligt den nya bestämmelsen i regel redan omfattats av straffansvar enligt tidigare gällande rätt. I framtiden kommer dessa gärningar endast att åtalas under en annan brottsrubricering. Den nya kriminaliseringens betydelse ligger därför främst i dess symbolvärde och i att den skapar större rättslig klarhet.